Community divergence in a tropical forest following a severe cyclone. (14th April 2014) - Murphy, Helen T.; Metcalfe, Daniel J.; Bradford, Matt G.; Ford, Andrew J.
Abstract Cyclones are relatively infrequent, may cause massive and widespread disturbance to tropical regions, and are recognized as important determinants of the structure of tropical rainforest communities. Climate change scientists predict that the intensity of cyclones will increase in the future; understanding the long‐term implications of these major disturbances for tropical forest composition and structure will be vital in anticipating and adapting to future changes and impacts. We established a long‐term monitoring site in a rainforest area impacted by severe tropical Cyclone Larry which crossed the North Queensland coast of Australia in March 2006. We monitored recruitment, growth and mortality of nearly 17 000 seedlings in 90 quadrats across the study area for almost 5 years following the cyclone and measured the impact of variation in cyclone disturbance and debris load on community diversity, composition and dispersion as the forest recovered. We show that the level of structural disturbance sustained by the forest has a strong and immediate influence on community dynamics. Quadrats in severely disturbed areas, which were characterized by multiple treefalls and extensive canopy loss, had higher levels of diversity and variation in community assemblage than quadrats in areas characterized primarily by branch loss and defoliation. A rapid divergence in community composition between quadrats in the most‐ and least‐severely disturbed areas resulted in the development of statistically distinct community states across relatively small scales. This provides further evidence that severe cyclones are important in maintaining species diversity in tropical forests.